2008
DOI: 10.1073/pnas.0705460105
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Black Death mortality with respect to preexisting health

Abstract: frailty ͉ paleodemography ͉ paleoepidemiology ͉ selective mortality

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
178
5
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(196 citation statements)
references
References 41 publications
8
178
5
5
Order By: Relevance
“…Similarly, it has been shown that epidemic mortality in historic populations was apparently not selective with respect to age and sex among adults [8][9][10][11][12]. Conversely, it was shown that mortality associated with the medieval epidemic was selective with respect to frailty [10,11].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, it has been shown that epidemic mortality in historic populations was apparently not selective with respect to age and sex among adults [8][9][10][11][12]. Conversely, it was shown that mortality associated with the medieval epidemic was selective with respect to frailty [10,11].…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, it was shown that mortality associated with the medieval epidemic was selective with respect to frailty [10,11]. Individuals who were in poor health before the epidemics were more likely to die than were their healthy peers [11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, new research is challenging our traditional interpretation of non-specific indicators of stress as measures of health status (Reitsema and McIlvaine 2014), including dental enamel defects (Hassett 2014;Hubbard et al 2009), periosteal reaction (e.g., DeWitte 2014a, 2014bDeWitte and Wood 2008;Weston, 2008Weston, , 2009Weston, , 2012, and porotic hyperostosis (McIlvaine 2013;Piperata et al 2014), as well as specific patterns of pathology that are diagnostic of metabolic conditions such as scurvy (Crandall and Klaus 2014) and anemia (Smith-Guzman 2015), and infections such as leishmaniasis (Marsteller et al 2011). The study of disease progression over the life course also is being examined more broadly in contemporary studies of paleopathology that also draw upon medical sources (e.g., Baker and Bolhofner 2013).…”
Section: Contemporary Directionsmentioning
confidence: 99%